Labor market mobility and the early-career outcomes of immigrant men - Mohsen Javdani; Andrew McGee (IZA Journal of Development and Migration, 2018)
We examine the role of between- and within-firm mobility in the early-career outcomes of immigrant men. Among Canadian workers with less than 10 years of potential experience, we find that visible minority immigrants were significantly less likely to have been promoted with their initial employers than similar white natives but were just as likely to have moved to new employers over the course of a year between interviews. White immigrants, on the other hand, were just as likely to be promoted as white natives but much more likely to move to new employers-suggesting that they enjoyed more overall mobility than white natives and other immigrants. We present tentative evidence linking these mobility patterns to differences in wage growth and occupational change between immigrants and natives. Overall, our findings suggest that the between- and within-firm mobility of white immigrants may play an important role in their relative economic success in Canada, while adding to growing evidence that visible minority immigrants experience frictions in the labor market that hinder their mobility and thus their economic prospects.
Keywords: J61; J71; 330; Promotions; Employer changes; Immigration; Visible minorities